2018
DOI: 10.17957/ijab/15.0640
|View full text |Cite
|
Sign up to set email alerts
|

Role of Reactive Oxygen Species and Contribution of New Players in Defense Mechanism under Drought Stress in Rice

Abstract: Rice (Oryza sativa) falls among the staple food crops in different parts of the globe. In current scenario of climate change, drought stress leads to significant decrease in crop production. It has negative effect on rice growth and development by affecting cellular, physiological and molecular processes. Photo-respiration increases under drought stress leads to overproduction of reactive oxygen species (ROS) in different organelles of the cell like chloroplasts, mitochondria and peroxisomes etc., which induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 123 publications
1
15
0
Order By: Relevance
“…Environmental stresses trigger several physiological and biochemical responses in plants as a strategy to withstand adverse circumstances [22]. Regarding biochemical responses to moisture deficit, plants accumulate solutes like proline, sugars, along with activation of antioxidant defense system [16,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental stresses trigger several physiological and biochemical responses in plants as a strategy to withstand adverse circumstances [22]. Regarding biochemical responses to moisture deficit, plants accumulate solutes like proline, sugars, along with activation of antioxidant defense system [16,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Drought is responsible for leaf shrinkage and it affects tillering capacity and photosynthesis in plants (Kramer & Boyer, 1995). During grain filling stage, water stress causes early senescence in plant which reduces its filling period (Plaut et al, 2004) leading to yield reduction (Qureshi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports revealed that flavonoids act as antioxidants to scavenge ROS [6,34,35]. To test whether the ROS levels can be affected in the quercetin-treated plants, we then used DAB and NBT staining methods to detect the H 2 O 2 and O 2 − levels in the primary root tips, respectively.…”
Section: Resultsmentioning
confidence: 99%